Intimate Partner Violence and Subsequent Depression in Women: A Systematic Review and Meta‐Analysis of Longitudinal Studies - Christopher B. Watson; Vicki Bitsika (Brain and Behavior)
ABSTRACT Introduction Intimate partner violence (IPV) and depression are global health concerns with high prevalence rates and substantial negative impacts on individuals and the wider community. Women are particularly vulnerable to both IPV victimization and depressive disorders, and both are recognized worldwide as priorities for women's health. The aim of this systematic review and meta‐analysis was to determine whether recent longitudinal empirical evidence supports exposure to IPV as a contributing factor to the subsequent onset of depression in women. Methods A search was performed in August 2024 of the Medline, PsychInfo, and EBSCOHost databases for longitudinal studies published after the year 2013, and 1193 studies were identified. Studies were included if they were written in English and measured IPV as an independent variable with depression as a dependent variable. Studies were excluded if depression was not measured separately from other variables or did not report primary quantitative data. Eleven studies with 118,544 female participants met the inclusion criteria for review. Results Ten of the 11 reviewed studies reported a statistically significant positive association between exposure to IPV and depression in women. A random effects meta‐analysis was used to generate pooled odds ratios from nine estimates, which demonstrated that female IPV survivors have significantly increased odds of developing subsequent depression (OR = 1.92, (95% CI: 1.28, 2.86); although, there was high heterogeneity across studies (I2 = 98.3%, p < 0.001). Ten of the 11 studies were from high‐income, industrialized countries, which limits the global application of these findings. Conclusions These findings suggest that IPV may be one of many contributing factors for depression in women. However, variability in the definition of IPV and inconsistent adjustment for confounders across studies limits firm conclusions. The findings of this review suggest that strategies to prevent IPV could play a role in reducing the prevalence of depression. They also support the inclusion of depression screening for survivors of IPV in clinical approaches and a review of the effectiveness of IPV‐related depression intervention strategies.